Razlike između transtorakalne ehokardiografije i transtorakalne ehokardiografije na hemodinamiku i odgovor na inflamatorni stres kod pacijenata sa teškom aortalnom stenozom - Deng, Fanxin; Chen, Aidong; Chen, Bin; Yang, Bo; Shi, Xiaoming; Xu, Zhipeng (Journal of Medical Biochemistry, 2025)
Background: Transcatheter aortic valve replacement (TAVR) is currently the main approach for treating severe aortic stenosis (AS), and preoperative echocardiography is a necessary measure. In this research, we analyzed the application value of transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) in TAVR, aiming to provide more reliable reference opinions for future clinical implementation of TAVR for patients with severe AS. Methods: 204 patients with severe AS who were treated with TAVR in our hospital from January 2022 to February 2024 were selected as the research subjects. Among them, 109 patients received TTE (TTE group), and another 95 patients received TEE (TEE group). Differences in the evaluation effects of preoperative echocardiography and multislice helical computed tomography (MSCT) in all patients were compared, and changes in echocardiographic parameters before and after surgery were observed. In addition, the differences in postoperative hemodynamics, cardiac function, stress response, inflammatory factors and pain mediators between the observation and TTE groups were compared. Results: No differences were identified in the evaluation of the aortic root between echocardiography and MSCT (P>0.05). After surgery, parameters such as LVESD and IVST decreased, while LVEF and AVA increased (P<0.05). The TEE group showed superior postoperative hemodynamics to the TTE group (P<0.05). There was no difference in cardiac function between the two groups (P>0.05), but IL-1β, IL-6, TNF-α, 5-HT, ET-1 and SP were lower in the TEE group than in the TTE group, whereas SOD was higher than in the TTE group (P<0.05). Conclusion: TTE and TEE has an excellent guiding effect on the implementation of TAVR in patients with severe AS, among which TEE is more helpful in improving the effectiveness and safety of TAVR.